Novel Fatty Acid Desaturase 3 (FADS3) Transcripts Generated By Alternative Splicing - Park, Woo Jung (2009)
Fatty acid desaturase 1 and 2 (FADS1 and FADS2) code for the key desaturase enzymes involved in the biosynthesis of long chain polyunsaturated fatty acids in mammals. FADS3 shares close sequence homology to FADS1 and FADS2 but the function of its gene product remains unknown. Alternative transcripts (AT) generated by alternative splicing (AS) are increasingly recognized as an important mechanism enabling a single gene to code for multiple gene products. We report the first AT of a FADS gene, FADS3, generated by AS. Aided by ORF Finder, we identified putative coding regions of eight AT for FADS3 with 1.34 kb (classical splicing), 1.14 (AT1), 0.77 (AT2), 1.25 (AT3), 0.51 (AT4), 0.74 (AT6), and 1.11 (AT7). In addition we identified a 0.51 kb length transcript (AT5) that has a termination codon within intron 8–9. The expression of each AT was analyzed in baboon neonate tissues and in differentiated and undifferentiated human SK-N-SH neuroblastoma cells. FADS3 AT are expressed in 12 neonate baboon tissues and showed reciprocal increases and decreases in expression changes in response to human neuronal cell differentiation. FADS3 AT, conserved in primates and under metabolic control in human cells, are a putative mediator of LCPUFA biosynthesis and/or regulation.